#### Answer

-1

#### Work Step by Step

$y^3+3xyz$ $\longrightarrow$substitute
=$(-1)^3+3(3)(-1)(0)$ $\longrightarrow$simplify
=$-1+0$
=$-1$

Published by
Pearson

ISBN 10:
0321955048

ISBN 13:
978-0-32195-504-3

-1

$y^3+3xyz$ $\longrightarrow$substitute
=$(-1)^3+3(3)(-1)(0)$ $\longrightarrow$simplify
=$-1+0$
=$-1$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.